Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Heterogeneity and chimerism of endothelial cells revealed by single-cell transcriptome in orthotopic liver tumors - Qi Zhao; Maria del Pilar Molina-Portela; Asma Parveen; Alexander Adler; Christina Adler; Hock E; Wei Wang; Min Ni; Yi Wei; Gurinder Atwal; Markus Mohrs; Gavin Thurston; et al. (Angiogenesis, 2020)
The liver is a common host organ for cancer, either through lesions that arise in liver epithelial cells [e.g., hepatocellular carcinoma (HCC)] or as a site of metastasis by tumors arising in other organs (e.g., colorectal cancer). However, the changes that occur in liver stromal cells in response to cancer have not been fully characterized, nor has it been determined whether the different sources of liver cancer induce distinct stromal changes. Here, we performed single-cell profiling of liver stromal cells from mouse models of induced spontaneous liver cancer or implanted colorectal liver metastases, with a focus on tumor endothelial cells (ECs). While ECs in liver tissue adjacent to cancerous lesions (so-called adjacent normal) corresponded to liver zonation phenotypes, their transcriptomes were also clearly altered by the presence of a tumor. In comparison, tumor EC transcriptomes show stronger similarities to venous than sinusoidal ECs. Further, tumor ECs, independent of tumor origin, formed distinct clusters displaying conserved “tip-like” or “stalk-like” characteristics, similar to ECs from subcutaneous tumors. However, they also carried liver-specific signatures found in normal liver ECs, suggesting an influence of the host organ on tumor ECs. Our results document gene expression signatures in ECs in liver cancer and show that the host organ, and not the site of tumor origin (liver versus colorectal), is a primary determinant of EC phenotype. In addition, primarily in tumors, we further defined a cluster of chimeric cells that expressed both myeloid and endothelial cell markers and might play a role in tumor angiogenesis.

Plant invasion into high elevations implies adaptation to high UV-B environments: a multi-species experiment - Lena Y. Watermann; Maria Hock; Christopher Blake; Alexandra Erfmeier (Biological Invasions, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Exotic plant species are locally adapted but not to high ultraviolet‐B radiation: a reciprocal multispecies experiment - Maria Hock; Rainer W. Hofmann; Caroline Müller; Alexandra Erfmeier (Ecology, 2019)
Ultraviolet ( UV ) radiation intensities differ among global regions, with significantly higher levels in the southern hemisphere. UV ‐B may act as an environmental filter during plant invasions, which might particularly apply to plant species from Europe introduced to New Zealand. Just like for any other abiotic or biotic filter, successful invaders can cope with novel environmental conditions via plastic responses and/or through rapid adaptation by natural selection in the exotic range. We conducted a multispecies experiment with herbaceous plants in two common gardens located in the species’ native and exotic ranges, in Germany and New Zealand, respectively. We used plants of German and New Zealand origin of eight species to test for adaptation to higher UV ‐B radiation in their new range. In each common garden, all plants were exposed to three radiation treatments: (1) ambient sunlight, (2) exclusion of UV ‐B while transmitting ambient UV ‐A, and (3) combined exclusion of UV ‐B and UV ‐A. Linear mixed‐effect models revealed significant effects of UV ‐B on growth and leaf traits and an indication for UV ‐B‐induced biomass reduction in both common gardens pointing to an impact of natural, ambient UV radiation intensities experienced by plants in the northern and in the southern hemisphere. In both common gardens, the respective local plants (i.e., German origins in Germany, New Zealand origins in New Zealand) displayed enhanced productivity and aboveground biomass allocation, thus providing evidence for recent evolutionary processes in the exotic range. Genetic differentiation between different origins in consequence of divergent local selection pressures was found for specific leaf area. This differentiation particularly hints at different selective forces in both ranges while only little evidence was found for an immediate selective effect of high UV ‐B intensities in the exotic range. However, reaction norm slopes across ranges revealed higher plasticity of exotic individuals in functional leaf traits that might allow for a more sensitive regulation of photoprotection measures in response to UV ‐B. During the colonization, New Zealand populations might have been selected for the observed higher phenotypic plasticity and a consequently increased ability to successfully spread in the exotic range.